Influence of Board Reformation on the Stock Returns: an Event Study - Kohli, Bindya; Pillai, Deepa (International Journal of Engineering and Technology, 2018)
Investor sentiments pertaining to stocks are propelled by the contentions of financial sector reforms, fiscal policy and management change. Any uncertainty has a significant impact on the stock prices and returns accruing to the company. The paper examines the effect of change in management on the stock returns of a corporate entity. Organizational performance is dependent on the realization of the numerous roles the board of directors are entrusted with. Any change in the composition of the board through the resignation, retirement or ouster can thus have a significant impact on the stock prices and returns accruing to the company. It is anticipated that voluntary resignations, age related turnovers have small or negative impact on the stock price reactions. The paper investigates the impact of the ouster of the Chairman of the Tata group on the volatility of the daily prices and returns of four companies under the Tata umbrella. Event study methodology has been adopted following the market model of return generating process. Investors react to the market information thereby affecting the security prices positively or negatively during the event window. The findings disclose market sentiments are affected on the occurrence of the event though the acceptance of the event may be unforeseen.Â
Keywords: Abnormal returns; Board composition; Daily average returns; Event study; Governance; Stock returns